(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
Effect of three levels of irrigation viz., no irrigation (I0), irrigation once a month (I1) and irrigations twice a month (I2) on some growth attributes and leaf yield and some of its components of five mulberry varieties were studied in field condition. Significant effect of irrigation on relative growth rate (RGR), net assimilation rate (NAR), leaf area ratio (LAR), and relative leaf growth rate (RLGR) was observed. lrrigation also had significant effect on leaf yield and some of its components. The overall results indicated that twice irrigations in a month with mulberry variety BM-4 could be used for higher leaf yield. Key words: Mulberry; lrrigation; Growth parameters; Leaf yield DOI: 10.3329/bjsir.v45i4.7331 Bangladesh J. Sci. Ind. Res. 45(4), 331-336, 2010